Peran Advokat Sebagai Penegak Hukum Menghadapi Transnational Crimes Di Era Globalisasi - Lumbuun, T. Gayus (LAW REVIEW, 2004)
The United Nations Convention against Transnational Organized Crime was adopted by the General Assembly at its Millennium meeting in November 2000. It will be opened for signature at a high level conference in Palermo, Italy in December 2000. it is the first legally binding United Nations instrument in the field of crime. It must be signed and ratified by 40 countries before it comes into force. States party to the Convention would be required to establish in their domestic laws four criminal offences: 1. participation in an organized criminal group; 2. money laundering; 3. corruption; and 4. obstruction of justice. It is hoped that upon ratification the Convention will emerge as the main tool Â of the international community for fighting transnational crime.